The practicality of Cyperaceae popular scientific books in mangrove areas to college students’ criticial thinking skill - Musliha Musliha; Dharmono Dharmono; Badruzsaufari Badruzsaufari (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Critical thinking is one of the fundamental competencies needed by humans in the 21st century to produce quality human resources which can be seen in the implementation of the Tri Dharma Higher Education activities, it is necessary to develop learning resources that can direct students to improve and bring up knowledge, attitudes and critical thinking skills. One of the learning resources that can train students' critical thinking skills is a learning resource in the form of popular scientific books based on local potential which is presented and described in simple sentences, looks attractive and easy to understand and in accordance with the characteristics of critical thinking skills to facilitate students in the learning process. This study aims to describe the practicality of the popular scientific book Cyperaceae in the Mangrove area of Sungai Bakau Village on students' critical thinking skills. Data on the practicality of BIP were obtained from individual tests to determine student readability using a readability questionnaire, small test and field test to determine the practicality of expectations and actual practicality using student response questionnaires and observations on the implementation of BIP use using an implementation questionnaire. Research respondents are students who have passed the Higher Plant Botany course with research design development through formative evaluation from Tessmer.Abstrak Berpikir kritis merupakan salah satu kompetensi fundamental yang diperlukan manusia di abad 21 untuk menghasilkan SDM yang berkualitas yang terlihat dalam pelaksanaan kegiatan Tri Dharma Perguruan Tinggi maka perlu adanya pengembangan sumber belajar yang dapat mengarahkan mahasiswa untuk meningkatkan dan memunculkan pengetahuan, sikap dan keterampilan berpikir tingkat kritis. Salah satu sumber belajar yang dapat melatihakn keterampilan berpikir kritis mahasiswa adalah sumber belajar berupa buku ilmiah populer berbasis potensi lokal yang disajikan dan dijabarkan dengan kalimat sederhana,tampilan menarik dan mudah dipahami serta sesuai dengan karakteristik keterampilan berpikir kritis untuk memudahkan mahasiswa dalam proses pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan buku ilmihah populer Cyperaceae di daerah Mangrove Desa Sungai Bakau terhadap keterampilan berpikir kritis mahasiswa. Data kepraktisan BIP diperoleh dai uji perorangan untuk mengetahui keterbacaan mahasiswa menggunakan angket keterbacaan, uji kecil dan uji lapangan untuk mengethaui kepraktisan harapan dan kepraktisan aktual menggunakan angket respon mahasiswa dan observasi terhadap keterlaksanan penggunaan BIP menggunakan angket keterlaksanaan. Responden penelitian merupakan mahasiswa yang telah lulus mata kuliah Botani Tumbuhan Tinggi dengan desain penelitian pengembangan melalui evaluasi formatif dari Tessmer.